PENDETEKSIAN FRAUD DENGAN HUKUM BENFORD - Theresia Hesti Bwarleling (Jurnal Akuntansi Bisnis, 2017)
The objectives of this research is to find the answers of whether Benford’s Law can be effectively used as one of the measurement of the audit planning instruments for determining whether the customs value of the sample company is acceptable or not. To answer this question, the first thing to do is to find out the custom value of the sample company. To asses whether a particular custom value is acceptable or not then a digital analysis vehicle called Benford’s Law as well as a number of statistical test is used. Assessment is done to detect fraudulent data as part of risk management in audit planning in order to choose company. The result of the research shows that Benford’s Law can be neither be used effectively to assess whether customs of the sample company is acceptable or not, nor can it be used effectively as one of the audit planning instrument for these company. However this result applies only to the sample tested and can not be generalized.Keywords: Fraud, Benford’s Law, Audit Planning